PENDIDIKAN MULTIKULTURAL - Tayyeb, Thamrin (Universitas Islam Negeri Alauddin Makassar, 2017)
Multicultural education can be described as education that awakens learners to cultural diversity, human rights or the reduction of various kinds of prejudices in building a just and prosperous society. This modeling education, trying to see how family roles awaken individuals in the family, that cultural diversity must be acceptable to every individual family. This education, an alternative solution for learners who do not want to work together, just because of differences in culture, ethnicity, and beliefs. Ideal education strengthens the sense of brotherhood in various differences.